2017
DOI: 10.1371/journal.pone.0177742
|View full text |Cite
|
Sign up to set email alerts
|

Using NextRAD sequencing to infer movement of herbivores among host plants

Abstract: Herbivores often move among spatially interspersed host plants, tracking high-quality resources through space and time. This dispersal is of particular interest for vectors of plant pathogens. Existing molecular tools to track such movement have yielded important insights, but often provide insufficient genetic resolution to infer spread at finer spatiotemporal scales. Here, we explore the use of Nextera-tagmented reductively-amplified DNA (NextRAD) sequencing to infer movement of a highly-mobile winged insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 77 publications
1
17
0
Order By: Relevance
“…A new genotyping technology, NextRAD, can overcome these constraints by fragmenting and ligating adaptor sequences to genomic DNA through engineered transposomes (Nextera DNA Library Prep Reference Guide), and requires very small amounts of DNA (less than 50 ng) ( Russello et al 2015 ), enabling acquisition of sequence data from small organisms that could not be studied using RAD applications. This approach has been successfully utilized to study fine-scale population genetics and diversity in a mosquito species ( Emerson et al 2015 ) and the potato psyllid ( Fu et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A new genotyping technology, NextRAD, can overcome these constraints by fragmenting and ligating adaptor sequences to genomic DNA through engineered transposomes (Nextera DNA Library Prep Reference Guide), and requires very small amounts of DNA (less than 50 ng) ( Russello et al 2015 ), enabling acquisition of sequence data from small organisms that could not be studied using RAD applications. This approach has been successfully utilized to study fine-scale population genetics and diversity in a mosquito species ( Emerson et al 2015 ) and the potato psyllid ( Fu et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a genotyping-by-sequencing variant protocol that requires low input DNA, Nextera-tagmented reductively amplified DNA (nextRAD) [ 46 48 ], has been developed. In this protocol, the Nextera kit (Illumina, Inc.) is used to tagment genomic DNA via in vitro transposition and attach short adaptors.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies were well designed for characterizing the species composition of economically important B. tabaci communities and genetic differences at continental and global scales, there remains a need for studies that leverage genome-wide datasets to address questions about the importance of local movements for B. tabaci ecology and evolution. Such studies in other insect systems have revealed colonization of crop fields from specific non-crop host plant reservoirs [ 4 ], identified sibling pairs separated by distances > 3 km and uncovered previously hidden patterns of isolation by distance [ 91 ], and shown how the spatial configuration of crop fields can impede or enhance gene flow among pest populations in certain environments [ 5 , 92 ].…”
Section: Single Nucleotide Polymorphismsmentioning
confidence: 99%
“…Such knowledge can be difficult to obtain; however, for widely dispersing insects whose populations cannot readily be tracked across agricultural landscapes [ 1 , 2 , 3 ]. In these systems, population genetics approaches, which use observations of genetic diversity and differentiation among populations based on molecular markers to infer evolutionary processes acting on populations, can delineate which host plants are being attacked [ 4 ], how far and regularly pests are moving across landscapes [ 5 , 6 ], and whether insecticide resistance (or other traits allowing adaptation to new management techniques) tend to rapidly spread among and across populations [ 7 ]. One such agricultural pest for which a substantial body of literature has emerged, using population genetics approaches, is the sweet potato whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) cryptic species complex.…”
Section: Introductionmentioning
confidence: 99%